Insomnia as a Risk Factor for Cardiovascular Disease Among Adults in Eastern Indonesia - Heltty Heltty; Firman Firman; Elmukhsinur Elmukhsinur; Wa Ode Aisya Zoharia; Noviati Noviati (Althea Medical Journal, 2026)
Background: Insomnia is a common sleep disorder with increasing prevalence among adults and has been linked to a higher risk of cardiovascular disease (CVD). This study aimed to investigate the association between insomnia severity and CVD risk among adults.Methods: This correlational study with a cross-sectional design involved adults aged 30–59 years with insomnia. Participants were recruited using convenience sampling, at Kota Hospital and Bahteramas Hospital, Kendari, Indonesia, between November 2023 and April 2024. Insomnia severity was measured using the Insomnia Severity Index (ISI), and CVD risk was assessed using the Framingham Risk Score. Data were analyzed using the Pearson chi-square and multinomial logistic regression analysis. Results: Of the 144 respondents, the majority were female (59.0%), aged >50 years (62.5%) with a mean age of 49.63±10.08 years. Gastroesophageal reflux disease (GERD) was the most common comorbidity (39.6%), and 57.6% were smokers. Most respondents had moderate insomnia (87%) and low CVD risk (66%). Severe insomnia was more frequently observed among participants with moderate and high CVD risk. A significant positive relationship was found between insomnia severity and CVD risk (p=0.000, r=0.669), with insomnia explaining 50.2% of the variance in CVD risk.Conclusion: Insomnia is significantly associated with cardiovascular risk and may represent a modifiable lifestyle-related risk factor. Improving sleep quality may contribute to healthier lifestyles and reduced CVD risk.